Monitoring the physical fitness of students aged 10-15 and 15-18 during online education - Olena Nesen; Lesia Korobeinikova; Iryna Ivanyshyn; Olga Goncharova (Physical Culture, Recreation and Rehabilitation)
Background and Study Aim. The necessity to switch to online learning is closely related to the need to ensure the safety of students, which is jeopardized by the military conflict in Ukraine. In the context of online learning, diagnosing the physical fitness of students becomes more challenging, creating problems for physical education teachers. The purpose of the study is to suggest alternatives to physical fitness tests for students that can be adequately conducted at home.